Editorial [Hot topic: Myostatin: Regulation, Function and Applications (Guest Editor: Se-Jin Lee)] - Lee, Se-Jin (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2010)
It has now been 13 years since the original report in 1997 of the discovery of myostatin and its function as a negative regulator of muscle mass [1]. Since that initial report, an enormous amount of effort in both the academic and the biotechnology/pharmaceutical research communities has been directed at understanding the biology of myostatin and developing strategies for exploiting its biological activity for clinical applications. A PubMed search with the term “myostatin” now lists almost 900 papers, and collectively, these papers have provided numerous insights into the regulation and function of myostatin as well as the consequences of manipulating myostatin activity in both normal and disease settings. These insights have fueled the development of therapeutic agents targeting this signaling pathway, and at least four companies have entered clinical trials with myostatin inhibitors to combat muscle loss. In this issue of Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry, we have assembled a group of thought leaders to review and assess the progress that has been made to date in this field. In the first article in this collection, I summarize what is currently known about the mechanisms by which myostatin activity is regulated extracellularly by inhibitory binding proteins, and I discuss the implications of these regulatory mechanisms both with respect to therapeutic development and with respect to the physiological function of myostatin in regulating the balance between muscle and fat. The second article, written by Anthony Otto, Antonios Matsakas, and Ketan Patel, addresses the role of myostatin in regulating myogenesis. The authors synthesize data obtained in multiple species regarding the expression pattern of myostatin during development, the mechanisms by which myostatin expression is regulated, and the function of myostatin in establishing the proper numbers and types of muscle fibers. This article is followed by two articles describing potential applications of targeting the myostatin pathway for treating muscle degenerative and wasting conditions. In the first, Kathryn Wagner summarizes efforts to date investigating the potential beneficial effects of blocking myostatin signaling in various neuromuscular diseases, including muscular dystrophy, spinal muscular atrophy, and amyotropic lateral sclerosis. In the second, Hilary Wilkinson summarizes what is known about the role that myostatin may play in age-related muscle loss, or sarcopenia, and the effects of inhibiting this pathway in rodent models of sarcopenia. The fact that levels of myostatin signaling can have such profound effects on overall muscle mass has implications for the physiology of muscle not only in terms of its contractile function but also in terms of its metabolic activity, the latter of which is the focus of the next two articles. In one article, Alexandra McPherron reviews what is known about the metabolic functions of myostatin and the highly related protein, GDF-11, and in the other, Powen Tu, Shalender Bhasin, and Wen Guo discuss the cardiometabolic effects of myostatin inhibition. In the final article in this collection, Michel Georges summarizes the enormous amount of data that have been obtained from multiple species in which naturally occurring myostatin mutations have been identified and discusses the prospects of targeting myostatin signaling for livestock production.